Self concept, self efficacy, and interpersonal communication effectiveness of student - Yulikhah, Safitri; Bukhori, Baidi; Murtadho, Ali (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
Successful interpersonal communication is one of the determinants of success factors of preaching, counseling, and learning. However, the data showed that not all students can deliver effective interpersonal communication. It can be developed if students have self-concept and self-efficacy. This study aims to examine the effects of self-concept and self-efficacy on students' interpersonal communication. The subjects of this study were 342 students of the Walisongo State Islamic University of Semarang, who were selected using the cluster random sampling technique. Data were collected using three psychological scales, namely self-concept scale, self-efficacy, and effective interpersonal communication scale. Simple regression techniques and multiple regressions were used for analyzing the data. The results of the study showed that self-concept partially influenced the effectiveness of the students' interpersonal communication, contributing by 12.7%. In line with the finding, self-efficacy also has a contribution to it by 12%. Also, self-concept and self-efficacy simultaneously had contributions to the effectiveness of the students' interpersonal communication as much as 12.2%.